Language-Specific Existential Sentence Types: a Case Study of Lithuanian - Kalėdaitė, Violeta (Kalbotyra, 2008)
The article is devoted to the analysis of a specific syntactic structure in Lithuanian, the BKI construction. This type of sentence is also attested in Russian, where it has got a wide coverage. The BKI construction in Lithuanian is made up of the following elements: (i) a form of the existential verb būti ‘be’, (ii) the k-word, and (iii) the infinitive. The type is attested both in positive and negative forms. The peculiarity of the construction has been noted by a number of Lithuanian scholars, however, no link has been recognized between the semantic content of the sentence, the existential verb būti ‘be’, and the syntactic structure of the construction. The data used for the analysis (2,000 entries) are taken from Dabartinės lietuvių kalbos tekstynas at http://donelaitis.vdu.lt. In the article the author offers a new approach to the analysis of the BKI construction and claims that it represents a language-specific existential structure. Evidence is presented to the effect that the BKI construction in Lithuanian is a syntactic synonym of the existential type ‘proper’. [...]